Translating poetic discourse : questions on feminist strategies in Adrienne Rich - Díaz-Diocaretz, Myriam (Critical theory, 1985)
Translating Poetic Discourse argues in favor of a critical model that bridges between translation and women's studies on theoretical and practical levels. It proposes key-elements to be integrated into the problem of interpretation of contemporary poetry by women, and discusses the links between gender markers and the speech situation in feminist discourse as a systematic problem. This book will be of interest to scholars of Translation Studies, Women's Studies, Poetry, Comparative Literature and Discourse.